A systematic review of the evidence for pharmacist care of patients with dyslipidemia - Charrois, Theresa; Zolezzi, M.; Koshman, S.; Pearson, G.; Makowsky, M.; Durec, T.; Tsuyuki, R. (Pharmacotherapy Publications, Inc., 2012)
Study Objective: To evaluate the effect of pharmacist care on patients with dyslipidemia. Design: Systematic review of 21 randomized controlled trials. Patients: A total of 5416 patients who received enhanced pharmacist care or standard care as part of a research study. Measurements and Main Results: Nineteen databases and four trial registries were systematically searched from inception through February 21, 2010, with an update in September 2011. In addition, Web sites of relevant professional associations, scientific meetings, and research groups were reviewed, and manual searches of select journals were performed. A total of 8771 articles were identified, and 21 studies included. Data from the studies were analyzed using a random-effects model. The primary outcome measure assessed was the difference between the groups (pharmacist intervention vs standard care) in low-density lipoprotein cholesterol (LDL) level at the end of follow-up. Secondary outcome measures included the difference between the groups at the end of follow-up in total cholesterol, high-density lipoprotein cholesterol, and triglyceride levels; and the proportion of patients who achieved target lipid parameters, underwent lipid panel measurements, adhered to therapy, and/or were instructed to change their lipid-lowering therapy.At the end of follow-up, the mean LDL level was 10.7 mg/dl lower in the enhanced pharmacy care groups compared with the standard care groups (95% confidence interval [CI] –16.9 to –4.6 mg/dl), with moderate heterogeneity. The mean total cholesterol level was significantly lower in the enhanced pharmacy care groups compared with the standard care groups; however, these results were highly heterogeneous. Patients who received enhanced pharmacist care were also more likely than those receiving standard care to achieve target lipid parameters (odds ratio [OR] 2.46, 95% CI 1.43–4.25) and to have a lipid panel ordered or recommended by a pharmacist during the study (OR 2.05, 95% CI 1.30–3.24). Patients in the pharmacist intervention groups were almost twice as likely as patients in the standard care groups to have a change in lipid-lowering therapy (OR 1.82, 95% CI 1.09–3.06). Adherence data could not be analyzed.Conclusion: This systematic review showed that enhanced pharmacist care improves lipid parameters, notably LDL levels, in patients with dyslipidemia. These results point to the benefit that pharmacist care can provide across the spectrum of dyslipidemia management, from screening patients to treating them to assisting them in the attainment of clinical targets.